PREDICTION OF TOBACCO PRODUCTION USING THE METHOD SINGLE SPECTRUM ANALYSIS (SSA) - Ardaniah Hazrah; Rina Widyasari (UIN Sumatera Utara, 2023)
ABSTRACTThe increasing population growth in North Sumatra Province every year has an impact on increasing the need for staple sources for daily life in North Sumatra, so it is necessary to do a forecast to anticipate food shortages in the future. This study aims to determine the results of tobacco production in North Sumatra Province in 2024 and the level of accuracy of the methods used. The results of the study obtained the prediction of rice production in North Sumatra Province in 2024 using the Singular Spectrum Analysis (SSA) method, respectively from Quarter I to Quarter III, of 665 tons, 725 tons, and 740 tons, with a level of forecasting accuracy based on the standard MAPE value obtained of 15.78%. The MAPE value obtained is less than 10% and close to 0%, meaning that the SSA method with window lengths of 9 and 7 groups is very accurate for predicting tobacco production in North Sumatra Province.